نظرية الرفاهية الاقتصادية في الاقتصاد الإسلامي ودور الزكاة في الرفاه الاجتماعي - أحمد عمر بابيكر, محمد (University of Eloued جامعة الوادي, 2014)
يعالج البحث قضية الرفاهية الاقتصادية ويحاول تطبيقها على المجتمع المسلم, وذلك عن طريق السياسات الشرعية ومؤسسة الزكاة. وتبرز أهميته فى إبراز مقدرة الاقتصاد الإسلامي على تحقيق ذلك, ويهدف إلى تأسيس نظرية إسلامية فى الرفاهية الاقتصادية. ويفترض مقدرة الاقتصاد الإسلامى على تأسيس نظرية فى الرفاهية الاجتماعية. المنهج المختار هو التحليلى والاستنباطى. وقد توصل البحث إلى نتائج متعددة أهمها: - قدرة الاقتصاد الإسلامى على إيجاد أسس نظرية وتطبيقية تحقق رفاهية اجتماعية لكل أفراد المجتمع. Abstract The research deals with the issue of economic welfare and tries to implement it on Muslim’s society. This will be done through Sharia’a’s policies and Zakat’s institution. Significance of the research is to extract the ability of Islamic economic to achieve this task. It aims to construct an Islamic theory in economic welfare. It postulates the ability of Islamic economy to construct a theory in social welfare. Methodology chosen is the analytical and induction. Various outcomes have been reached. Important of which is: - ability of Islamic economic to find theoretical and applicable bases which achieve social welfare for all society’s individuals.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: نظرية الرفاهية الاقتصادية - الاقتصاد الإسلامي- الزكاة - الرفاه الاجتماعي